ANALYSIS OF SALES PROMOTION IMPACT ON CUSTOMER LOYALTY AMONG DANA E-WALLET USERS AT UNIVERSITAS NEGERI MAKASSAR - Lely Novia; Quena Rahmawati Dahayu; Indrawaty Asfah (Study Program of Sharia Business Management , Faculty of Islamic Economics and Business, 2026)
This study aims to examine the effect of sales promotions on customer loyalty among DANA e-wallet users who are students at Makassar State University. This study uses a descriptive quantitative approach. Data were collected through questionnaires from 187 students who actively use the DANA e-wallet. The sales promotion variable was measured based on the level of promotion, discounts, and gifts offered by DANA, while customer loyalty was measured through satisfaction and repurchase intention. Data were analyzed using SPSS version 22 with multiple linear regression to determine the relationship between sales promotion and customer loyalty. The results show a significant influence between sales promotions and customer loyalty (significance value < 0.05). This indicates that the more effective DANA's promotional strategies are, the higher the loyalty level of student users. These findings emphasize the importance of well-designed promotional strategies to increase customer loyalty in the e-wallet ecosystem, especially among students as potential users. This research provides practical insights for e-wallet providers to develop more customer-oriented and impactful promotional programs. In conclusion, sales promotions have a significant effect on the loyalty of DANA e-wallet users in the student community at Makassar State University.